2019
DOI: 10.1016/j.ijid.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s sarcoma-associated herpesvirus seropositivity is associated with type 2 diabetes mellitus: A case–control study in Xinjiang, China

Abstract: To assess the potential relationship between Kaposi's sarcoma-associated herpesvirus (KSHV) infection and type 2 diabetes mellitus (DM-2) in Xinjiang, China. Methods: A case-control study of consecutively included DM-2 patients and normal controls was conducted among the Uygur and Han populations in Xinjiang Uygur Autonomous Region, China. Blood samples were collected and KSHV seroprevalence, antibody titers, and viral load were investigated. Logistic regression analysis and multiple linear regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…The KSHV pathway contains genes related to IFN antiviral response, inflammatory cytokines, and cell proliferation pathways [ ]. Interestingly, the association between KSHV and DM was previously reported by observational studies ( 107 , 108 ). Cui et al described that patients with T2DM had an elevated risk of KSHV ( 107 ).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The KSHV pathway contains genes related to IFN antiviral response, inflammatory cytokines, and cell proliferation pathways [ ]. Interestingly, the association between KSHV and DM was previously reported by observational studies ( 107 , 108 ). Cui et al described that patients with T2DM had an elevated risk of KSHV ( 107 ).…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, the association between KSHV and DM was previously reported by observational studies (107,108). Cui et al described that patients with T2DM had an elevated risk of KSHV (107). Accordingly, Piras et al showed 58% of T2DM patients were seropositive for KSHV vs. 27% of the healthy subjects (108).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cui et al have recently reported that T2DM patients have an increased risk of infection with Kaposi's sarcoma-associated herpesvirus (KSHV or HHV-8) ( 241 ). They further showed that the viral load and antibody titers are positively correlated with blood glucose levels ( 241 ).…”
Section: Effects Of T2dm On the Susceptibility Of Patients To Infectimentioning
confidence: 99%
“…Cui et al have recently reported that T2DM patients have an increased risk of infection with Kaposi's sarcoma-associated herpesvirus (KSHV or HHV-8) ( 241 ). They further showed that the viral load and antibody titers are positively correlated with blood glucose levels ( 241 ). Diabetic patients also have been shown to have an increased risk of infection with the severe acute respiratory syndrome coronavirus (SARS-CoV) ( 242 ), Middle East respiratory syndrome coronavirus (MERS-CoV) ( 243 ), SARS coronavirus 2 (SARS-CoV-2) ( 21 , 22 ), hepatitis C virus (HCV) ( 244 – 246 ), and West Nile virus encephalitis (WNVE) ( 247 ).…”
Section: Effects Of T2dm On the Susceptibility Of Patients To Infectimentioning
confidence: 99%